Leverage deficit and firm acquisitions - Moss, Lukas (2022)
This study analyzes the effect a firm’s deviation from its target capital structure has on the value of the pursued acquisitions. By first predicting annually the optimal debt ratio, the leverage deficit for each company was determined relative to its actual debt level. The leverage deficit was then used to examine its influence on the quality of the respective acquisitions by the firms. The results obtained from the target capital structure regression are in line with previous empirical findings about target leverage determinants. The analysis of the value-enhancing effect of the leverage deviation yielded estimates that were either insignificant or indicated an adverse impact of the leverage deficit. In conclusion, no evidence is found supporting the hypothesis that the leverage deficit of a firm has a positive effect on the value of its acquisition targets, suggesting further investigation of the effects of leverage in the context of firm acquisitions.